2008
DOI: 10.1007/s10517-008-0019-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis and coronary atherosclerosis: Protective antioxidant effect of bilirubin

Abstract: Increased concentration of lipid peroxidation products in patients with primary biliary cirrhosis is related to elevation of serum lipid content, but not to activation of lipid peroxidation. Hyperbilirubinemia in patients with primary biliary cirrhosis is accompanied by a decrease in the concentration of lipid peroxidation products and increase in antioxidant activity of blood serum. Antioxidants play a major role in the prevention of atherosclerosis. We hypothesized that the absence of increased risk of ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Confirming several other reports, our study shows a lower risk for myocardial ischemia in patients with cholestatic liver disease versus NASH/cryptogenic liver disease . These results suggest the need for an individualized approach to cardiac assessment and risk stratification of liver transplant candidates with NASH.…”
Section: Discussionsupporting
confidence: 90%
“…Confirming several other reports, our study shows a lower risk for myocardial ischemia in patients with cholestatic liver disease versus NASH/cryptogenic liver disease . These results suggest the need for an individualized approach to cardiac assessment and risk stratification of liver transplant candidates with NASH.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is consistent with the absence of increased risks of myocardial infarction, stroke, and preclinical carotid atherosclerosis among patients with PBC and hypercholesterolemia [25][26][27]. The explanation for this protective effect remains largely unknown but may involve antioxidant properties of bilirubin [28], prevention of low-density lipoprotein oxidation by lipoprotein X [29], elevated serum levels of adiponectin [30], and FXR and TGR5 receptor activation [18].…”
Section: Discussionsupporting
confidence: 72%
“…Abbasi et al performed Mendelian randomization in a prospective cohort of 3381 participants, used rs6742078 located in UGT1A 1, and found that elevated STBC is causally associated with the risk of DM [ 25 ]. Several studies also found that low-grade inflammation plays a critical role in the development of diabetic retinopathy [ 16 , 26 ]. Bilirubin also has anti-inflammatory properties through interfering with the expression of cell adhesion molecules, complement activity, and T cell differentiation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%